Politics, Imagination, and the Problem of Antiquation: Embracing Old and New Materialisms - Bazzul, Jesse (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
Political imagination has never been more important, yet it is very often foreclosed in conservative educational spaces. It’s important to question the occlusion of political imagination from both science and education on a general level—something STEM-types are actively discouraged from thinking about. In order for education fields to progress and face the crises of our century there must be space to dream/think/imagine ‘the political’ along infinite horizons. This essay is an attempt to clear some space for political imagination by problematizing quick dismissals of older critical perspectives (e.g. materialisms), and suggests that any turn to ontology needs to be continually interpreted and politicized. Giving space to politics and imagination is vital as educators dream about different futures in the ruins of capitalism. This paper speaks to the ‘ontological turn’ that is still occurring in various academic disciplines in the humanities and social sciences.